2011
DOI: 10.5352/jls.2011.21.12.1659
|View full text |Cite
|
Sign up to set email alerts
|

Development of a SCAR Marker Linked to Male Fertility Traits in 'Jinkyool' (Citrus sunki)

Abstract: In Citrus, an F1 segregation population of 150 plants was constructed from a cross between 'Kiyomi' (C. unshiu × C. sinensis) carrying the male sterility trait and 'Jinkyool' (C. sunki). Sequence-related amplification polymorphism (SRAP) combined with bulked segregant analysis was used to develop markers linked to male fertility. In the F1 population, 66 out of 150 seedlings had aborted anthers and the ratio of male sterile plants to fertile plants in the progenies matched the expected Mendelian segregation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Chae et al reported the development of DNA marker linked to male fertility of C . sunki [ 29 ]. Quantitative trait locus (QTL) analysis of the reduced pollen production trait will clarify the number of genes likely to be involved in regulation of the trait.…”
Section: Resultsmentioning
confidence: 99%
“…Chae et al reported the development of DNA marker linked to male fertility of C . sunki [ 29 ]. Quantitative trait locus (QTL) analysis of the reduced pollen production trait will clarify the number of genes likely to be involved in regulation of the trait.…”
Section: Resultsmentioning
confidence: 99%
“…Yamamoto et al [ 8 ] demonstrate the interaction between nuclear and cytoplasmic genes by reciprocal hybridizations. Subsequent research has pointed to the involvement of nuclear genes in male sterility [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. DNA marker analysis for nuclear and cytoplasmic genomes and genome-wide SNP marker analysis showed that CMS in the satsuma was derived from its seed parent, the ‘Kishu’ mandarin ( C. kinokuni ), and that the nuclear genes come from the male parent, ‘Kunenbo’ mandarin ( C. nobilis ) [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yamamoto et al (1997) demonstrate the interaction between nuclear and cytoplasmic genes by reciprocal hybridizations. Subsequent research has pointed to the involvement of nuclear genes in male sterility (Chae et al, 2011;Dewi et al, 2013bDewi et al, , 2013aNakano et al, 2001;. DNA marker analysis for nuclear and cytoplasmic genomes and genome-wide SNP marker analysis showed that CMS in the satsuma was derived from its seed parent, the 'Kishu' mandarin (C. kinokuni), and that the nuclear genes come from the male parent, 'Kunenbo' mandarin (C. nobilis) .…”
Section: Introductionmentioning
confidence: 99%